2020
DOI: 10.7202/1067310ar
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation par approche statistique de l’impact des changements climatiques sur les ressources en eau : application au périmètre du Gharb (Maroc)

Abstract: Afin d’évaluer l’impact des changements climatiques sur les ressources en eau, nous réalisons dans ce travail une analyse statistique spatio-temporelle de certaines variables climatiques du bilan hydrique. En effet, pour comprendre les variations climatiques ayant eu lieu dans le passé, l’analyse statistique doit se faire sur des séries chronologiques de données représentatives aussi bien sur le plan spatial que temporel. Toutefois, ces séries de données présentent souvent des lacunes dans les mesures et des i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…A significant regional precipitation breakpoint around 1973 was detected in the western High Atlas and Anti-Atlas Mountains (Abahous et al 2018). In contrast, Acharki et al (2019) showed homogeneous precipitation over the Gharb plain with no breakpoint from 1974 to 2016. Similarly, using the same statistical tests (Pettitt), Bakreti et al (2013) detected no breakpoint in a precipitation time series from the Tafna basin (Algeria), perhaps because their time series began (1974 for Acharki and 1976 for Bakreti) during a phase previously shown by the analysis of the SPI to be a dry period.…”
Section: Variability Changes and Breakpoints In Hydrology And Climate...mentioning
confidence: 93%
See 1 more Smart Citation
“…A significant regional precipitation breakpoint around 1973 was detected in the western High Atlas and Anti-Atlas Mountains (Abahous et al 2018). In contrast, Acharki et al (2019) showed homogeneous precipitation over the Gharb plain with no breakpoint from 1974 to 2016. Similarly, using the same statistical tests (Pettitt), Bakreti et al (2013) detected no breakpoint in a precipitation time series from the Tafna basin (Algeria), perhaps because their time series began (1974 for Acharki and 1976 for Bakreti) during a phase previously shown by the analysis of the SPI to be a dry period.…”
Section: Variability Changes and Breakpoints In Hydrology And Climate...mentioning
confidence: 93%
“…The Mediterranean region, in addition to having been heavily urbanised and impacted by human activities for centuries, is considered a 'hotspot' of climate change (Huebener & Kerschgens 2007;Hallett et al 2018;Naumann et al 2018) as it is strongly influenced by a significant increasing trend in air temperature and potential evapotranspiration (Chaouche et al 2010;Rosmann et al 2016;Acharki et al 2019) and by changes in precipitation intensity, duration and frequency (IPCC 2013). Water resources and hydrological processes depend greatly on not only climate but also on human activities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The MICE approach was developed by B. Rubin in 1987 and is also called the "multiple sequential regression imputation". It is a semi-parametric imputation approach that allows the suggestion of a model closer to the nature of the data [65]. Its principle is based on the imputation of incomplete variables [66][67][68].…”
Section: Data Processingmentioning
confidence: 99%
“…It experiences a subhumid Mediterranean climate that is influenced by the ocean in the west, whereas its interior has a semi-arid climate [13]. Gharb's annual mean temperature is around 17.31-19.37 •C and annual precipitation is about 409-557 mm [14].…”
Section: Study Areamentioning
confidence: 99%